The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ijnss.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Concept analysis of coping with multiple sclerosis

Abstract: Objective The concept of coping with disease appears frequently in the literature; however, there is no precise definition of coping. The aim of this study is to clarify coping concept, and to identify its attributes, antecedents, and consequences in patients with multiple sclerosis. Methods Rodgers' evolutionary method of concept analysis was used to clarify the concept of coping. A literature review was conducted with key terms ‘multiple sclerosis’, ‘coping’, ‘adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…The selfcare agency and quality of life of the patients with MS decreased, and their adaptation levels were affected because of some factors, such as experiencing balance problems (27%), the use of a wheelchair (12%) and a walking stick (21%), wearing glasses (28%), the presence of family members who provided care (10%), being unemployed (54%), comorbidities (32%), being a primary school graduate (38%), having children (70%), being a dominant female participant (76%), and being younger than 45 years (62%). Besides, these findings have been supported by some studies reporting that the quality of life of patients with MS is lower than others 21,22 and by the study of Hyarat et al 15 conducted with patients with MS, which reported that patients with a low quality of life also showed a low level of adaptation to MS.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The selfcare agency and quality of life of the patients with MS decreased, and their adaptation levels were affected because of some factors, such as experiencing balance problems (27%), the use of a wheelchair (12%) and a walking stick (21%), wearing glasses (28%), the presence of family members who provided care (10%), being unemployed (54%), comorbidities (32%), being a primary school graduate (38%), having children (70%), being a dominant female participant (76%), and being younger than 45 years (62%). Besides, these findings have been supported by some studies reporting that the quality of life of patients with MS is lower than others 21,22 and by the study of Hyarat et al 15 conducted with patients with MS, which reported that patients with a low quality of life also showed a low level of adaptation to MS.…”
Section: Discussionmentioning
confidence: 55%
“…The statement in the literature that the quality of life of patients with MS is lower than others supports these findings. 15,20,21 In addition, Dehghani et al 22 stated that the adaptation levels of individuals who conceded the disease were strong and consistent. Multiple sclerosis causes depression, pain, and balance problems that disrupt the physical, social, and psychological independence of patients, 23 and these problems vary from person to person.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that emotional reactions and anxiety were expressed due to a sudden physical change during for example experiences of MS symptoms. As was shown by Dehghani et al 29 , the maintenance of emotional balance, acceptance of the disease and self-regulation are favorable factors for coping with MS. Our results as well show that emotional reactions related to general stress were expressed frequently. A new result we could add to literature is that emotional reactions to general stress seem to be a way to cope in persons with MS.…”
Section: Discussionmentioning
confidence: 79%
“…Quality assessing final articles selected for a principle-based concept analysis using recognised tools such as the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist (von Elm et al, 2007) for quantitative studies and the consolidated for reporting qualitative research (COREQ) checklist (Tong et al, 2007) for qualitative studies (e.g. Dehghani et al, 2018) were reviewed. Yet, existing tools are not suitable or developed for principle-based concept analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Principle-based concept analysis can include qualitative, quantitative and mixed-methods research and grey literature. Guidelines such as the Centre for Reviews and Dissemination guidelines for the University of York, UK (CRD, 2009) can be followed which have been used in a previous principle-based concept analysis (Dehghani et al, 2018). Other suitable guidelines include Cochrane (e.g.…”
Section: Phase 1: Preparation Phasementioning
confidence: 99%